Electroacupuncture Reduces Uterine Artery Blood Flow Impedance in Infertile Women - Ming Ho; Li-Chia Huang; Yin-Yi Chang; Huey-Yi Chen; Wei-Chun Chang; Tung-Chuan Yang; Horng-Der Tsai (Elsevier, 2009)
Objective: To evaluate the effects of electroacupuncture (EA) on pregnancy rate and uterine artery blood flow impedance in patients undergoing in vitro fertilization (IVF). Materials and Methods: This prospective, randomized trial was carried out in the IVF center of China Medical University Hospital in Taiwan, from February 1, 2004 to January 30, 2005. A total of 44 patients were enrolled in the study. Of these, 30 were allocated to acupuncture, and 14 were allocated to no acupuncture. EA was performed four times, twice a week for 2 weeks, from day 2 of the study to the day before oocyte retrieval. After patients felt the needle reaction, the needles were attached to an electrical stimulator for 30 minutes. Clinical pregnancy and pulsatility index (PI) of right and left uterine arteries before and after EA were measured. Results: There was no significant difference in pregnancy rate between the two groups (acupuncture group, 30%; non-acupuncture group, 28.6%). The mean PI of both uterine arteries was significantly reduced after EA (left uterine artery, 2.3 to 2.0; right uterine artery, 2.4 to 2.2). There was no significant change in PI in the group with no acupuncture (left uterine artery, 2.5 to 2.3; right uterine artery, 2.4 to 2.3). Conclusion: EA could be useful for reducing uterine artery blood flow impedance, but did not increase the pregnancy rate in patients undergoing IVF.